Safety and Security of the Environment for Flat Dwellers on the Granting of Building Rights Title (HGB) on Management Rights (HPL) for 80 Years - Alwaahab Agirda Nugraha Effendi (GoAcademica Research & Publishing, 2023)
The development of high-rise apartment buildings is an alternative solution to meet the housing and settlement needs. After the enactment of the Job Creation Law (UUCK), the Government issued Regulation No. 18 of 2021 concerning Management Rights, Land Rights, High-rise Apartment Units, and Land Registration. In this regulation, the period of Building Use Rights (HGB) over Management Rights (HPL) can be granted for 80 (eighty) years for the construction of high-rise apartments. This study was conducted to determine whether granting HGB over HPL for 80 (eighty) years is appropriate to be implemented and whether it potentially threatens the safety and environmental security of the high-rise apartment residents. The study results show that based on the prevailing regulations, granting HGB over HPL for 80 (eighty) years is appropriate because there is periodic inspection of the feasibility of the function every 5 (five) years as a requirement for certificate of feasibility of function (SLF) extension. However, in terms of building reliability, granting HGB over HPL for high-rise apartments for 80 (eighty) years still potentially poses a threat to the safety and environmental security of the residents because the building's capability will decrease in strength that affects the building's reliability. Another risk arises because the sanctions given for the negligence of periodic inspections on the building's reliability in the process of extending SLF are only in the form of administrative sanctions, so more severe sanctions such as criminal sanctions need to be imposed on violators.